Change Detection Using Landsat Data 2000 and Sentinel Data 2020 for Meghadrigedda Sub-Watersheds Using Hydrogeomorphology, NDWI and, NDVI, Visakhapatnam District, Andhra Pradesh-India - Usha Chirala (Current Advances in Geography, Environment and Earth Sciences Vol. 4, 2022)
With global warming and over-exploitation of water resources as a result of population growth and other challenges, several research are being conducted around the world to restore a balanced living between current water resources and their consumption. This study is based on a watershed of 366 square kilometers on a 1:50,000 scale 65O/1 SOI map surrounding the Meghadrigedda reservoir in the Visakhapatnam district of Andhra Pradesh, India. The watershed was divided into nine sub-watersheds, and hydrogeomorphology, drainage, drainage density, slope, NDVI, and NDWI of the study area were accomplished in ArcGIS 10.0 using Landsat data 2010 and Sentinel data 2020. For irrigation, drinking, and personal use, all of the villages in the catchment rely heavily on groundwater. Change detection was used to show the fall in surface water and groundwater as a result of increased built-up area, pond siltation, and a reduction in the number of ponds. Large-scale anthropogenic activities are taking place in the watershed. To keep the monsoon water flowing, the government must reduce built-up activity and desilt the ponds. The findings of the study can be used to plan and construct a sustainable basin area.